Phosphatidic acid produced by phospholipase D is required for hyphal cell‐cell fusion and fungal‐plant symbiosis. Issue 6 (12th February 2020) - Hassing, Berit; Eaton, Carla J.; Winter, David; Green, Kimberly A.; Brandt, Ulrike; Savoian, Matthew S.; Mesarich, Carl H.; Fleissner, Andre; Scott, Barry
Abstract: Although lipid signaling has been shown to serve crucial roles in mammals and plants, little is known about this process in filamentous fungi. Here we analyze the contribution of phospholipase D (PLD) and its product phosphatidic acid (PA) in hyphal morphogenesis and growth of Epichloë festucae and Neurospora crassa, and in the establishment of a symbiotic interaction between E. festucae and Lolium perenne . Growth of E. festucae and N. crassa PLD deletion strains in axenic culture, and for E. festucae in association with L. perenne, were analyzed by light‐, confocal‐ and electron microscopy. Changes in PA distribution were analyzed in E. festucae using a PA biosensor and the impact of these changes on the endocytic recycling and superoxide production investigated. We found that E. festucae PldB, and the N. crassa ortholog, PLA‐7, are required for polarized growth and cell fusion and contribute to ascospore development, whereas PldA/PLA‐8 are dispensable for these functions. Exogenous addition of PA rescues the cell‐fusion phenotype in E. festucae . PldB is also crucial for E. festucae to establish a symbiotic association with L. perenne . This study identifies a new component of the cell‐cell communication and cell fusion signaling network for hyphal morphogenesis and growth of filamentous fungi. Abstract : Phospholipase D hydrolyses phosphatidylcholine to produce phosphatidic acid, a lipid second messenger and free choline. Here we investigate the role of PLD and PA in a fungal endophyte of grasses, Epichloë festucae and the model organism Neurospora crassa . We found that one PLD isoform is required for normal polarized growth and hyphal fusion. In E. festucae this isoform is furthermore crucial for a mutualistic interaction with perennial ryegrass.